2006
DOI: 10.4161/cbt.5.1.2234
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional analysis of platelet-derived growth factor in uterine leiomyomata

Abstract: The expression of PDGF and its receptors in leiomyoma and myometrial tissue varied during the menstrual cycle. PDGF may play a role in the pathogenesis of leiomyomas through a mechanism involved in not only the proliferation of leiomyoma cells but also excessive expression of extra cellular molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 30 publications
2
36
0
3
Order By: Relevance
“…The expression of FGF receptor protein was also reported to be more intense in leiomyomas than in the myometrium (25). Another potent mitogen for smooth muscle cells is PDGF, its mRNA is expressed in both leiomyomas and in myometrium, and its receptor sites per cell are seen more in leiomyomas than in the myometrium (26,27). However, it appears that PDGF does not act alone, but acts in concert with other growth factors such as TGF-β, EGF, and the IGFs.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of FGF receptor protein was also reported to be more intense in leiomyomas than in the myometrium (25). Another potent mitogen for smooth muscle cells is PDGF, its mRNA is expressed in both leiomyomas and in myometrium, and its receptor sites per cell are seen more in leiomyomas than in the myometrium (26,27). However, it appears that PDGF does not act alone, but acts in concert with other growth factors such as TGF-β, EGF, and the IGFs.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-derived growth factor stimulates DNA and protein synthesis, increases collagen α1 expression, and modulates the rate of cell proliferation in myometrium and leiomyoma cells [13]. In this study, PDGF-A mRNA expression in leiomyoma and normal myometrium was decreased after treatment with SPRM; PCNA protein was increased in leiomyoma.…”
Section: Commentmentioning
confidence: 73%
“…Several growth factors, including epidermal (EGF) [9], insulin-like (IGF) [10,11], vascular endothelial (VEGF) [12], platelet-derived (PDGF) [13], and transforming (TGF)-β growth factors [14], are associated with leiomyoma growth. Furthermore, some apoptotic factors such as p53 tumor suppressor [15], B-cell lymphoma (Bcl)-2 [16,17], and tumor necrosis factor (TNF)-α [18] are involved in leiomyoma apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been shown that IGF-I treatment can increase leiomyoma proliferation [103,116,117], it remains to be clarified how progesterone regulation of IGFs contributes to leiomyoma growth. The differential expression of PDGFs in leiomyoma and myometrial cells is conflicting depending on the study [105,118122]. It has been shown that increased PDGF-BB expression occurs during the secretory phase compared to the proliferative phase in leiomyomas [118].…”
Section: Regulation Of Growth Factors and Their Receptors By Progestementioning
confidence: 99%